Leisure and Cultural Norms - Maryam Rafatjah (Taḥqīqāt-i Farhangī-i Īrān)
Leisure is one of the most important fields in the socio cultural studies which represent the cultural changes and new life styles. Since people in their leisure times have more freedom and less obligations so that most of them choose and do activities which are based on their values and interests and cultural tastes. Hence, the study of leisure among the youth which are a leading generation and represent the cultural changes of society sounds to be beneficial for recognizing the cultural trends and planning and policy making as well. So the main object of this research is to study the leisure patterns of non Tehranian students and recognizing their leisure problems. The study of leisure activities of students and the factors influencing it could help to know about their leisure needs and interests and examine their leisure problems more exactly. This research conducted on a probabilistic sample of dormitory students of the University of Tehran. The research findings show that in the spending of leisure times girls tend to the active ways and boys tend to amusing ways of spending leisure. On the whole boys use the leisure facilities of dormitory much more than girls. In addition, more than half of the students are not satisfied with the way they spend their leisure and the most important reason of their unsatisfying is mentioned the limitation of recreational facilities and financial problems. However the girls have confronted with more deprivations in recreational facilities and boys have more financial limitations. Finally the way of spending leisure times is related to the students\' concept of leisure, attitudes and values, life style, amount of religious commitment and the previous planning for leisure.